2020
DOI: 10.3390/catal10020181
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of HRP Enzyme onto a Magnetic Fe3O4 Np–PMMA Film via Casting with Sustainable Biocatalytic Activity

Abstract: Horseradish peroxidase (HRP) enzyme was effectively encapsulated onto an Fe3O4 nanoparticle–polymethyl methacrylate (PMMA) film via the casting method. The HRP was immobilized on the 0.5% Fe3O4Np–PMMA film and characterized by Fourier transform infrared spectroscopy and field emission scanning electron microscopy. Moreover, the reusability, thermal stability, optimum pH, optimum temperature, the influence of metal ions, and the effects of detergent and organic solvent were investigated. After optimizing the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…When α-amylase was immobilized following the same procedure as pullulanase, a similar shift of optimal temperature from 35 to 40 °C was observed (Figure S1). Also, similar improvements in thermal stability have been previously reported for various immobilized enzymes. , The change in optimal temperature observed here demonstrated that immobilized pullulanase was resistant to temperature increases, probably due to the immobilization-associated modifications to the physicochemical properties of the enzyme . Thus, with respect to industrial applications, immobilized enzymes are preferable to soluble forms, as the immobilized form can withstand the high temperatures that are important for enzyme catalysis …”
Section: Resultssupporting
confidence: 85%
“…When α-amylase was immobilized following the same procedure as pullulanase, a similar shift of optimal temperature from 35 to 40 °C was observed (Figure S1). Also, similar improvements in thermal stability have been previously reported for various immobilized enzymes. , The change in optimal temperature observed here demonstrated that immobilized pullulanase was resistant to temperature increases, probably due to the immobilization-associated modifications to the physicochemical properties of the enzyme . Thus, with respect to industrial applications, immobilized enzymes are preferable to soluble forms, as the immobilized form can withstand the high temperatures that are important for enzyme catalysis …”
Section: Resultssupporting
confidence: 85%
“…45 As a comparison, the K m value with TMB of the B, N-PdRu aerogels was similar to that of horseradish peroxidase (HRP) and the K m of H 2 O 2 was nearly 100 times lower than the corresponding value of HRP, suggesting that B, N-PdRu aerogels have a better affinity for H 2 O 2 and TMB, as shown in Table 1. 46 As compared with some other reported nanozymes, the B, N-PdRu aerogels have a more superior peroxidase-like property.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“… Efficient removal of phenol in the presence of hydrogen peroxide. Removal of wastewater aromatic pollutants [123] Fe 3 O 4 –graphene nanocomposite Trametes Versicolor laccase APTES Stability and activity of the immobilized nanobiocatalyst was markedly increased than that to free laccase. Retained about 70% of its relative activity after incubating at 55 °C for 2 h, while only 48% of activity was recorded by the free laccase under identical time duration.…”
Section: Mof-modified Mnps For Enzyme Immobilizationmentioning
confidence: 98%